Toleransi Galur Harapan Padi Sawah (Oryza sativa L.) pada Persaingan dengan Gulma Echinochloa crus-galli - ,, Usman; Purwoko, Bambang Sapta; Syukur, Muhamad; Guntoro, dan Dwi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTBarnyard grass (Echinochloa crus-galli (L.) P. Beauv.) is a major weed competitor to rice production in Indonesia. In order to develop integrated weed management program, a research to select competitive rice lines to E. crus-galli was conducted in a green house of Indonesian Centre of Agricultural Biotechnology and Genetic Resource Research and Development Bogor. The research design was split plot with four replications, E. crus-galli was designed as the main plot (rice without E. crus-galli compared rice with four E. crus-galli per pot), and the sub-plots were 25 genotypes (23 lines, 1 tolerant variety and 1 sensitive variety). Level of tolerance was determined by the reduction percentage of grains weight, the number of productive tillers and dry matter weight. The results showed that rice competition with E. crus-galli reduced plant height, productive tiller numbers, filled spikelet numbers per panicle, dry matter weight and dry grain weight. Three lines, i.e., IR10L-155, IR10L-133 and BIO-R84-1 were classified as tolerant, 19 lines were moderate and 3 lines were sensitive to E. crus-galli competition.Keywords: Barnyard grass, competition, sensitive line, yield reduction